A theoretical model of the antecedents and outcomes of employee engagement: Dubin's method. Issue 3 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to propose a theoretical model that links the major antecedents, outcomes, and moderators of employee engagement.Design/methodology/approach – This paper uses the first part of Dubin's two‐part, eight‐step theory‐building methodology, and builds on existing research and empirical studies on engagement. In particular, the following five steps of the Dubin's methodology are addressed in this study: units (or concepts) of the theory, laws of interaction among the units, boundaries of the theory, system states of the theory, and propositions of the theory.Findings – The proposed theoretical model of employee engagement identifies job design and characteristics, supervisor and co‐worker relationships, workplace environment, and HRD practices as the major antecedents to employee engagement. The paper also proposes that job demands and individual characteristics act as moderators to the relationships between job design and characteristics, supervisor and co‐worker relationships, workplace environment, and employee engagement. Finally, it is proposed that employee engagement is related to three major organizational outcomes: job performance, turnover intention (inverse relationship), and organizational citizenship behavior.Originality/value – This paper addresses the paucity of structured literature on the antecedents and outcomes of employee engagement and presents a comprehensive, holistic model that offers a logical ground on which empirical indicators and hypotheses could be further identified and tested to verify the theory.